Implementasi Kebijakan Perwali No 79 Tahun 2022 tentang Penurunan Angka Stunting Melalui Pendampingan 1000 Hari Pertama Kehidupan di Kota Surabaya - Fara Dina Zachrawan; Agus Sukristyanto; Muhammad Roisul Basyar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The Surabaya City Government has achieved a significant level of success in reducing stunting rates due to the existence of various institutions that help overcome the stunting problem. Therefore, the City of Surabaya is quite good at providing initiatives that meet the objectives. In the process of dealing with the stunting problem, the Surabaya City government launched the latest regulation, namely Mayor Regulation No. 79 of 2022 concerning the acceleration of stunting reduction in the city of Surabaya. This research is qualitative research. Qualitative research is a type of research that applies description and analysis. The results of the research conclusions that have been carried out show that the implementation of Perwali No. 79 of 2022 policy regarding reducing stunting rates through assistance for the first 1000 days of life in the city of Surabaya can be successful because the variables from Michael Hill and Peter Hupe's theory can work well. This is also proven by the existence of the Policy Characteristics variable which is the aim of the policy being passed, namely reducing the stunting rate in the city of Surabaya.